Political parties of Asia and the Pacific: A reference guide (Longman, 1992)
The book contains background data on its country, including its recent history, constitutional structure, and recent election results; part-by-party data, providing for significant parties as appropriate: name in English and vernacular, address, leadership, orientation, history, structure, membership, publications, international affiliations; listing of minor and defunct parties; principal illegal organizations; indexes of personal names and parties